The Urgency of Legal Regulation On Investigator Authorization To Seize And Obtain Original Notarial Deeds - Fauza Shofia; Herlindah; M. Sudirman (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study examines the urgency of regulating and harmonizing the authority for the seizure and confiscation of notarial minutes in the Indonesian legal system. Minutes of deeds, as part of notarial protocol, have a special character as authentic evidence containing high evidentiary value, official confidentiality, and the legal interests of the parties. On the other hand, the need to enforce criminal law requires access to these documents, especially in the context of proving cases. This condition creates a gap between regulations in criminal procedure law and notarial law, especially regarding the authority of the Notary Honorary Council and the Chief Justice of the District Court. This study aims to analyze the philosophical, sociological, and juridical basis of these regulations, and formulate an appropriate form of harmonization to create legal certainty, justice, and benefit. The research method used is normative juridical with a statutory and conceptual approach, which examines various related legal norms and relevant legal doctrines. The results of the study indicate that the current regulations still cause partial disharmony, especially regarding the mechanism for confiscating original minutes of deeds, which has not been explicitly regulated. Therefore, normative harmonization is needed that places protection of deed minutes as a primary principle, while still allowing limited scope for seizure under exceptional circumstances. This harmonization must emphasize the functional relationship between the authority of the Notary Honorary Council as an ethical-professional filter and the Chief Justice of the District Court as a judicial supervisor, thus creating a balance between the protection of the notary's office and the effectiveness of criminal law enforcement